Tourism entrepreneurship typologies and their spatial analysis as input for the proposal of a municipal tourism product - Case study: county of Dota, Costa Rica: Spatial analysis of economic microentrepreneurship typologies with tourism potential in the county of Dota, Costa Rica - Avendaño-Leadem, Daniel (2021)
This article outlines part of the experience of the academic extension project entitled "Experiential tourism and biocultural heritage in Los Santos: community organization for innovation and chaining of the offer of tourism goods and services" of the National University of Costa Rica (UNA). Special emphasis is given towards the methodological approach applied in the identification and classification of the microentrepreneurships associated with tourist activity in the county of Dota and its patterns of spatial behavior. This approach generated a spatial analysis of the tourist offer that serves as a basis for decision-making processes related with the planning and management of the tourism sector of Dota county.